Red-Hot Selling : Power Techniques That Win Even the Toughest Sale. (AMACOM, 2010)
No matter what, where, and to whom you sell, everything you do fits into one of three phases of the sales process: Planning, Execution, and, Closing. True red-hot sellers know exactly what each phase encompasses, and the rest of us can learn in the time it takes to read this ultra-practical book. "Red-Hot Selling" presents a simple, start-to-finish sales process for new sales professionals and veterans alike. "Red-Hot Selling" also includes the author's powerful three-tiered planning process, proprietary tools including the Meeting Management Worksheet, and the best closing techniques in the business - plus can't-miss secrets for distinguishing your product or service in a competitive market. Selling may be tough, but it's not complicated. With this one-of-a-kind guide, you can streamline your job, kick-start your career, and send your earnings sky-high!